A PEMANFAATAN APLIKASI CANVA UNTUK PEMBUATAN CONTENT MARKETING DI SMK YPUI PARUNG - Septa; Syndhe Qumaruw Syty (Abdi Jurnal Publikasi, 2023)
The development of the internet makes it easy to communicate without limits. Physically, we can communicate in different places. The internet creates many conveniences for users in helping their daily activities. Content Marketing is a marketing activity that involves creating, curating, distributing and amplifying content that is interesting, relevant and useful to specific groups, in order to create talk about the content. One of the many applications that have been present in the world of technology is Canva. Canva is an Application or Web site or application that provides tools for creating graphic designs and online publications. The advantages of the Canva application are that it makes it easier for someone to make the design they want or need, such as; creation of posters, certificates, infographics, video templates and so on provided in the Canva application. The purpose of this PKM is to introduce the Canva application and the creation and use of the Canva application to create marketing content. Therefore we lecturers feel we have to introduce current technological developments, especially regarding the use of the Canva application. We hope that the PKM that has been implemented can increase students' knowledge in terms of using the Canva application to create their own marketing content. The result of this research is that this Community Service provides training to students at SMK YPUI Parung by utilizing the Canva application for content marketing creation. relatively easy.